Synthesis and Phase Transition Study of New Mesogence Derived from 1, 4-Phenylenediamine - Nisreen H. Karam (Journal of Global Pharma Technology, 2016)
This work include synthesized and characterization the compound [I] by reaction 1,4-phenylenediamine with chloro acetic acid  then this compound  reaction with methanol in present  sulfuric acid to synthesized ester compound [II] after that reaction with hydrazine hydrate to synthesized acide hydrazide [III] and the later compound reaction with substituted acetophenone[IV]n to synthesized substituted acetophenone hydrazones[V-XI]. In addition synthesized4-formylpyrazole derivatives [XII-XVIII] via cyclisation substituted acetophenone hydrazones [V-XI] with Vilsmeier-Haack reagent DMF/POCl3. The compounds characterized by melting points, FTIR, 1HNMR and mass spectroscopy. The mesomorphic behavior studied by using polarized optical microscopy and differential scanning calorimetry. Keywords: Liquid crystals, 4-formylpyrazole, 1, 4-phenylenediamine, Mesomorphic properties.